Influencia De La Tasa De Interés Real En La Inversión Privada En El Ecuador (2000-2014) - Romel Jimbiquiti Puenchera; Eduardo Zurita Moreano; Dante Ayaviri Nina; Gabriela González Bautista; Ma Eugenia Borja Lombeida (European Scientific Journal, ESJ, 2017)
Since the dollarization in Ecuador, the interest rate and investment rate has picked up as the economy grows. The present research explains the behavior of the investment as a function of the interest rates, through the neoclassical theory of Jorgenson. This model argues that to maximize corporate profits, it is necessary to define a production function consistent with the maximization principle. The research looks for a positive relationship between the product (Y) and the private investment (IP). In this context, the real interest rate (ir), which represents the cost of the use of capital, has a negative relation according to the empirical evidence in favor of Jorgenson's neoclassical theory.